Nilai-Nilai Dakwah dalam Gurindam 12 Pasal 2 Karya Raja Ali Haji - Muhammad Chairil Zanata; Toni Hartono; Vitra Ardiansyah; Rafi Alfikri; Alnita Rahmaranti (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2025)
Gurindam Dua Belas by Raja Ali Haji is not merely an old poetic work, but a living heritage whose values remain relevant across time. Through its concise and meaningful verses, it conveys profound guidance on the relationship between humans and God, as well as the importance of practicing the pillars of Islam as a pathway to a meaningful life. This study focuses on the dakwah values contained in the second passage of Gurindam Dua Belas, which addresses prayer, fasting, almsgiving (zakat), pilgrimage (hajj), and recognition of God (ma‘rifat). This research employs a descriptive qualitative approach with semantic analysis through library research to interpret the linguistic meanings and identify the dakwah values embedded in the text. The findings indicate that the second passage of Gurindam Dua Belas emphasizes the significance of ma‘rifat to Allah, as well as the practice of prayer, fasting, zakat, and hajj as foundational elements for shaping faith, moral character, and the spiritual responsibility of a Muslim.